Numeracy Literacy Skills of Grade XII Students of Sma Negeri 7 Manado Through Explanatory Texts Using the Project Based Learning Model - Mandey, Josepha Claudia; Iroth, Santje; Ratu, Donal M. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study was conducted at SMA Negeri 7 Manado with the aim of describing the literacy and numeracy skills of grade XII students through the application of the Project Based Learning (PBL) model in learning explanatory texts. The subjects of the study consisted of 24 students who took part in the learning process that began with orientation, motivation, and explanation of the material, followed by group discussions and presentations. The results of the analysis showed that students had good writing and reading skills, but still needed to improve their numeracy skills in the context of numeracy literacy. The results of the literacy and numeracy ability test showed an average student score of 70.33%, which was categorized as